2022
DOI: 10.3389/fonc.2022.938392
|View full text |Cite
|
Sign up to set email alerts
|

The independent adverse prognostic significance of 1q21 gain/amplification in newly diagnosed multiple myeloma patients

Abstract: Objective1q21 gain/amplification (1q21+) is a common abnormal karyotype in multiple myeloma, and its proportion in Chinese patients is much higher. If 1q21+ is included as one of the poor prognostic factors, it will greatly increase the proportion of high-risk patients in newly diagnosed multiple myelome (NDMM) patients. Therefore, the poor prognostic significance of 1q21+ is still controversial. This study mainly analyzed the clinical characteristics, treatment response and prognostic significance of 1q21+ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In recent years, 1q21+ has been identi ed as a potential poor prognostic factor [22,26], but the importance of 1q21 copy number in MM patient prognosis remains contradictory. You H et al [10] reported that the 1q21 amp had a shorter PFS than the 1q21 gain, but not the OS. Wang YT et al [6] considered that amp 1q21 alone correlated with shorter PFS and OS compared with gain 1q21 alone and no FISH abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, 1q21+ has been identi ed as a potential poor prognostic factor [22,26], but the importance of 1q21 copy number in MM patient prognosis remains contradictory. You H et al [10] reported that the 1q21 amp had a shorter PFS than the 1q21 gain, but not the OS. Wang YT et al [6] considered that amp 1q21 alone correlated with shorter PFS and OS compared with gain 1q21 alone and no FISH abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The main types of 1q21+ are isochromosomes, duplications, or jumping translocations, leading to the chromosomal instability of MM cells, which may be due to the genetic complexity and heterogeneity of patients carrying multiple copies of 1q21 and multiple genes. Several studies have identi ed the poor prognostic impact of 1q21 accompany [10][11][12], but the signi cance of copy number and clone size remains con icting [13,14]. The presence of 1q21+ may also be associated with other HRCAs, such as t(4;14) and t(14;16), or with 13q deletion[6, [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There are also differences with the aforementioned views. Several studies have revealed that the prognosis of patients with MM is worse when 1q21 copy number ≥4; for instance, You et al (28) revealed that 1q21 amplification had worse PFS than 1q21 gain (24 months vs. not reached, P=0.0403). Neben et al (77) discovered that a 1q21 copy number of three has a marginal negative effect, and having more than three copies significantly reduces PFS and OS.…”
Section: Impact Of 1q21 + On Prognosismentioning
confidence: 99%
“…In recent years, the introduction of autologous hematopoietic stem cell transplantation (ASCT), immunomodulatory drugs (IMiDs), proteasome inhibitors (PIs), and an anti-CD38 monoclonal antibody have greatly improved the outcomes of patients with MM (23)(24)(25)(26). However, the overall survival (OS) of patients with MM and 1q21 + remains to be improved (27,28). In the present review, the pathogenesis and clinicopathological features of MM patients with 1q21 + were reviewed, the key data of 1q21 + on the prognosis of patients with MM were summarized and the clinical treatment significance of MM patients with 1q21 + were clarified, for the purpose of providing reference for clinicians to develop treatment strategies targeting 1q21 + .…”
Section: Introductionmentioning
confidence: 99%
“…Differently from previous scores, abnormalities of 1q were included in the R2-ISS, as also recommended by NCCN MM Panel [ 21 ], without a distinction between gain (3 copies) and amplification (>3 copies), although this would further improve the risk stratification. It was recently described that amp1q and its main clone position could be significantly associated with prognosis results, in comparison with gain1q [ 22 , 23 , 24 , 25 ], even if the biological meaning of amp1q remains difficult to determine. A recent retrospective experience confirmed the greater role of the association of high risk feature rather than a single one, but also the size of high risk clone influenced prognosis [ 26 ].…”
Section: Improvements In Risk Stratificationmentioning
confidence: 99%